1997
DOI: 10.1111/j.1525-1594.1997.tb03717.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Centrifugal Blood Pump Based on the Motor Current

Abstract: In this study, centrifugal pump performance was examined in a mock circulatory loop to derive an automatic pump rotational speed (rpm) control method. The pivot bearing supported sealless centrifugal pump was placed in the left ventricular apex to aorta bypass mode. The pneumatic pulsatile ventricle was used to simulate the natural ventricle. To simulate the suction effect in the ventricle, a collapsible rubber tube was placed in the inflow port of the centrifugal pump in series with the apex of the simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…In controlling the pump rpm, as demonstrated in the previous study (9,10), bypass flow and motor current waveforms of the tripod pump showed a strong correlation under all conditions. Thus, a similar analysis as proposed previously can be applied to control the pump rpm to prevent the suction effect in the ventricle as well as to optimize the bypass flow level.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In controlling the pump rpm, as demonstrated in the previous study (9,10), bypass flow and motor current waveforms of the tripod pump showed a strong correlation under all conditions. Thus, a similar analysis as proposed previously can be applied to control the pump rpm to prevent the suction effect in the ventricle as well as to optimize the bypass flow level.…”
Section: Discussionsupporting
confidence: 67%
“…Based on the theoretical study conducted earlier, it was revealed that the significant waveform deformation does exist when the WDI value was above 0.2 (9,10). Thus, the threshold level of 0.2 was used to determine the presence of waveform deformation based on the FFT analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recent attempts have been able to physiologically mimic the atrium, ventricle, and vascular components, through the controlled use of pneumatic or hydraulic drives for flow, along with air tight integrated chambers to produce vascular resistance and compliance [19]. Although mock circulation loops provide a suitable test platform to evaluate cardiac assist devices [20,21] and their controllers performance [22,23], it has difficulty to produce complex nonlinear CV functions and implies high cost and compound mechanisms [24]. By focusing our attention on DMVA, it has not been shown how the mechanical interaction of these systems directly affects the complete mock circulatory system.…”
Section: Mock Modelsmentioning
confidence: 99%
“…Many of the publications related to VAD control do not describe controllers in the classical sense, but rather present algorithms with which suction can be detected (5,(7)(8)(9)(10)(11)(12)(13)(14)(15). Many of the publications related to VAD control do not describe controllers in the classical sense, but rather present algorithms with which suction can be detected (5,(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%